2017
DOI: 10.15403/jgld.2014.1121.262.myo
|View full text |Cite
|
Sign up to set email alerts
|

Is Heller Myotomy Better than Balloon Dilation? A Meta-Analysis

Abstract: Background & Aim: Endoscopic balloon dilation (EBD) and laparoscopic Heller myotomy (LHM) are the most commonly performed treatment options for achalasia. Decision between these treatment options is difficult. The aim of this meta-analysis was to evaluate the efficacy of EBD compared to LHM.Methods: The electronic databases PubMed, Embase and Cochrane Controlled Trials Registry were systematically searched for the period between January 1, 1976 and December 31, 2015. Meta-analysis was performed using the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
3
0
5
Order By: Relevance
“…Historically, HM has been the gold standard treatment for achalasia [12 -18]. HM improves symptoms in 89 % of patients, and combined with fundoplication, is a very safe operation with a mortality rate of 0.1 % [19]. Since 2008, POEM has proven its efficacy in the treatment of achalasia and it is now considered an alternative first-line therapy by many.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, HM has been the gold standard treatment for achalasia [12 -18]. HM improves symptoms in 89 % of patients, and combined with fundoplication, is a very safe operation with a mortality rate of 0.1 % [19]. Since 2008, POEM has proven its efficacy in the treatment of achalasia and it is now considered an alternative first-line therapy by many.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, according to the results of one of the prospective multicenter randomized trials, 2 years after LHM, 10% of patients developed significant recurrent symptoms of AC [12]. According to the data of the meta-analysis conducted by Illés A et al (2017), the effectiveness of LHM exceeded that of PD by the duration of remission and the reduction in the frequency of relapses in AC [9]; whereas according to the results of Cheng JW et al (2017), there were no significant differences between LHM and PD in 2-year and 5-year remission periods. This study showed that any type of treatment may be offered as initial treatment of AC [13].…”
Section: Resultsmentioning
confidence: 99%
“…Cicatrical changes in the gastroesophageal junction and persistent esophageal expansion are indications for surgical treatment with the use of modern laparoscopic and endoscopic techniques. The choice of surgical method depending on manometric subtypes determining the response to treatment is critical [9,10,11].…”
Section: Problem Statement and Analysis Of The Latest Researchmentioning
confidence: 99%
“…Традиционно наиболее часто используемые варианты лечения -это баллоная пневмокардиодилатация (ПКД) и лапароскопическая миотомия Геллера (ЛМГ) [8].…”
Section: актуальностьunclassified
“…По результатам одного из проспективных, многоцентровых рандомизированных исследований было доказано, что через 2 года у 10 % пациентов наблюдались значительные рецидивные симптомы после ЛМГ [2]. По данным мета-анализа, проведенного [8], эффективность ЛМГ превосходит эффективность ПКД по продолжительности ремиссии и снижению частоты рецидивов, в то время как нет никакой разницы в безопасности развития осложнений между двумя группами лечения [8]. В то время как по данным [4] существенных различий между ЛМГ и ПКД в 2-х летнем и 5-летнем периодах ремиссий не наблюдалось.…”
Section: актуальностьunclassified